PERAN KADERISASI PARTAI POLITIK KOTA MAKASSAR DALAM PENENTUAN CALON ANGGOTA LEGISLATIF PERSPEKTIF SIYASAH SYARIYYAH - Hamdi, Ahmad Fuad; Sakka, Rahman (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This research explores the role of political party cadreship in producing legislative candidates aligned with siyasah syariyyah principles. It examines how cadreship influences the selection of candidates based on Islamic political values, particularly in Makassar. Employing a field research method and a syar’i-normative juridical approach, the study reveals that political parties implement democratic and transparent processes, selecting candidates based on qualifications, integrity, and commitment. Supportive factors include programs, visions, and candidates' track records, while lack of public support hinders progress. From the fiqh siyasah syar’iah perspective, cadreship is essential in shaping candidates with integrity, reflecting Islamic justice through fair, transparent selection and comprehensive education. These findings highlight the importance of enhancing accountability and public trust in the political process, suggesting that the model used in Makassar could improve democratic practices in other regions